Analyzing Student Learning Gains to Evaluate Differentiated Teacher Preparation for Fostering English Learners' Achievement in Linguistically Diverse Classrooms. (September 2019) - Lavery, Matthew Ryan; Nutta, Joyce; Youngblood, Alison
Researchers compared pre/post classroom assessment scores of n = 8, 326 K-12 students taught by n = 288 teacher candidates to determine if a differentiated teacher education program prepared them to support English learners' (ELs) achievement in classrooms including native and nonnative speakers of English. Candidates in Group 1 comprised academic subject (secondary mathematics, science, and social studies) teacher candidates, who completed six teacher preparation courses with 15 key assignments that included a focus on ELs. Certification areas for Group 2 candidates include language arts instruction (elementary, early childhood, and secondary English language arts). Group 2 candidates completed from 12 to 15 courses with 41 to 50 key assignments that included a focus on ELs. Results indicate that teacher candidates in both groups helped narrow the gap between ELs and non-ELs from pretests to posttests. ELs performed no differently when taught by candidates from either group. Implications for teacher preparation are discussed.